2018
DOI: 10.1152/ajpgi.00295.2017
|View full text |Cite
|
Sign up to set email alerts
|

Young mice expel the tapeworm Hymenolepis diminuta and are protected from colitis by triggering a memory response with worm antigen

Abstract: Infection with helminth parasites reduces the severity of concomitant inflammatory disease in adult mice. There is an alarming increase of inflammatory bowel disease (IBD) in children. It is important to determine whether helminth therapy would be of value in pediatric IBD and whether triggering immunological memory to the worm would be anticolitic. Three-week-old (young) and eight-week-old (adult) Balb/c mice were infected with H. diminuta, and infectivity and T helper 2 (Th2) immunity were assessed. Other mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Crohn’s disease (CD) is a chronic dysregulated inflammatory disease of intestinal tract. Several studies have demonstrated the therapeutic potential of helminths in the treatment of colitis ( 25 27 ). Previously, we have demonstrated that infection of Trichinella spiralis reduce the severity of TNBS –induced colitis ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Crohn’s disease (CD) is a chronic dysregulated inflammatory disease of intestinal tract. Several studies have demonstrated the therapeutic potential of helminths in the treatment of colitis ( 25 27 ). Previously, we have demonstrated that infection of Trichinella spiralis reduce the severity of TNBS –induced colitis ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Reyes (2015) showed that CD19+ lymphocytes from H. diminuta –infected mice reduced the effects of DNBS, and thus promoted the suppression of colitis [ 115 ]. In turn, Arai et al (2018) showed that the H. diminuta antigen inducing an immune response in previously infected mice could be used to limit the severity of colitis regardless of the age of the host [ 118 ]. Graepel (2013) [ 111 ] found an exacerbation of the disease as a result of H. diminuta infection in a mouse with rheumatoid arthritis.…”
Section: Rat Tapeworm Hymenolepis Diminuta Rudomentioning
confidence: 99%
“…Three-week-old mice infected with H. diminuta were also protected from DNBS-induced colitis; however, the kinetics of this response differed from adult mice: young mice displayed less colitis when infected 10 days, but not 8 days, prior to treatment with DNBS [ 10 ]. This delay in the anti-colitic effect could be due to immaturity of the immune system in the young mouse, and it draws attention to the importance of the kinetics of the infection-colitis regimen.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with H. diminuta in the dextran sodium sulphate (DSS) [ 9 ] and di-nitrobenzene sulphonic acid (DNBS) [ 3 ] murine models of colitis were among the first to provide proof-of-concept data in support of helminth therapy to reduce the severity of colonic inflammation and concomitant signs of disease. While ongoing studies have confirmed the anti-colitic effect in the DNBS-model and revealed some of the nuances of the helminth–host interaction [ 10 , 11 , 12 ], two major questions remain unaddressed: both germane to helminth therapy: First, what is the temporal window of opportunity for H. diminuta to suppress colitis? Elucidation of the kinetics of infection in the context of inflammation can provide insight into host–parasite interaction and potentially reveal new targets for therapeutic intervention.…”
Section: Introductionmentioning
confidence: 99%